The effect of solid‐phase composition on the drying behavior of Markermeer sediment - Barciela‐Rial, M. (2020)
We studied the drying behavior of slurries of Markermeer sediments in the Netherlands having different solid compositions. Natural processes such as sand–mud segregation and oxidation of organic matter were mimicked to analyze the effect of changes in sediment composition. Evaporation experiments were performed with soft slurry samples using the Hyprop setup. Soil water retention curves (SWRCs) and hydraulic conductivity curves (HCCs) were determined as a function of the water ratio (WR, defined as volume of water/volume of solids). The sediment remained close to saturation until the end of the experiments. The Atterberg limits reduced significantly after sediment treatment involving drying at 50 °C, rewetting, and chemical oxidation. Furthermore, the oxidized sediment lost capacity to retain water. The SWRCs of sandy and oxidized clays were steeper, and fine‐textured sediments showed large water ratios. At low matric suctions, the water retention capacity of the upper sediment samples containing more labile organic matter was larger than that of the sediment underneath. Clear correlations were found between van Genuchten parameters and the degree of degradation of the organic matter. The hydraulic conductivity of fine‐textured samples with less labile organics was larger. The results give insight into the drying behavior of Markermeer sediment, currently used to build wetlands.